More obese, stunted Malaysian children - New Straits Times, (2012)
KUALA LUMPUR: The consumption of major food groups among Malaysian children is not in accordance to recommendation. While grains, meat and fish are consumed adequately or in excess, the consumption of fruits, vegetables and legumes, which are the major sources of dietary fibre, isway below the recommended 20g to 30g per day.